Analysis of Zakat and Tax Policies During the COVID-19 Pandemic - Nuzulia Nuzulia; Muhamad Nafik H Ryandhono (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
The relationship between zakat and tax dates back to the early days of the development of Islam. Zakat is one of the pillars of Islam whose obligation is absolute upon one's assets according to certain rules that have been regulated in the Al Quran and Hadith. Meanwhile, taxes are contributions issued by the public to be deposited with the government as state treasury, which is allocated to meet state expenditures. Since Covid-19 was declared a pandemic, Indonesia has been affected by the Covid-19 virus. Impact arising from various sectors such as health, education, socio-culture and economy. Various policies issued by the government to cut the spread of the Covid-19 virus, such as social distancing, studying or working from home and PSBB. Other than that, the government issued policies to restore the economy such as zakat and tax policies. This research was conducted to map and analyze zakat and tax policies issued by the government in order to reduce the economic impact of the Covid-19 pandemic. The research used a qualitative method with a descriptive approach obtained by studying the literature. The results of the study state that Indonesia has issued policies to help people affected by Covid-19 through zakat and tax policies. The research used a qualitative method with a descriptive approach obtained by studying the literature. The results of the study state that Indonesia has issued policies to help people affected by Covid-19 through zakat and tax policies. The research used a qualitative method with a descriptive approach obtained by studying the literature. The results of the study state that Indonesia has issued policies to help people affected by Covid-19 through zakat and tax policies.Keywords :Zakat, Tax, Policy, Impact, Pandemic